TECHNOLOGICAL AND ENVIRONMENTAL ASPECTS OF ILLEGAL INTERFERENCE IN MAIN PIPELINES - Бортняк, Олена Михайлівна; Школьний, Микола Петрович; Якимів, Йосип Васильович; Варик, Роман Степанович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Technical, organizational and legal aspects of detection of the illegal connections to the pipeline networks were reviewed basing on the analysis of current state of the problem of unauthorized interference with the main oil pipelines. Causes of accidents and potential environmental effects were enlightened. It was noted the need of improvement of technical systems for detection of oil leakages and the legal framework in the field of industrial safety of main pipelines as well as increasing responsibility for the intentional commission of unlawful acts of violation of the integrity of pipelines in order to capture transported product which have a sign of criminal character.